1976
DOI: 10.3758/bf03198705
|View full text |Cite
|
Sign up to set email alerts
|

Attention bands in absolute identification

Abstract: If both the number of one-dimensional signals and their range are sufficiently large (about 7 and 20 dB for loudness), the information transmitted in absolute identification is not much increased by increasing either variable (Miller, 1956; Braida & Durlach, 1972). The data can be represented in terms of Thurstonian discriminal dispersions in which the variance is proportional to the square of the signal range in decibels (Durlach & Braida, 1969;Gravetter & Lockhead, 1973). but it is by no means obvious what s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
101
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 11 publications
15
101
0
Order By: Relevance
“…Miller's (1956) classic paper focused on the limited channel capacity available to make absolute magnitude judgments (and explicitly linked signal variance with information transmission). In psychophysical work, Luce, Green, and Weber (1976) proposed that observers are able to strategically control attention bands, selectively monitoring a relatively narrow intensity range. Luce et al suggested that neural variability of the internal representation of intensities will be reduced within the favored attention band, yielding greater sensitivity as measured by signalto-noise ratio.…”
Section: Reference-point Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Miller's (1956) classic paper focused on the limited channel capacity available to make absolute magnitude judgments (and explicitly linked signal variance with information transmission). In psychophysical work, Luce, Green, and Weber (1976) proposed that observers are able to strategically control attention bands, selectively monitoring a relatively narrow intensity range. Luce et al suggested that neural variability of the internal representation of intensities will be reduced within the favored attention band, yielding greater sensitivity as measured by signalto-noise ratio.…”
Section: Reference-point Modelsmentioning
confidence: 99%
“…Human (and non-human) observers have limited capacity in working memory to maintain veridical estimates of magnitudes, which therefore vary in their precision (Miller, 1956). To partially compensate, observers focus attention on a favored region, or magnitude band, along the relevant continuum (Luce et al, 1976;Nosofsky, 1983). When making comparisons based on relative concepts, such as ''choose larger'' or ''choose smaller'', attention is guided by a reference point located at or near the end of the continuum cued by the form of the question (Holyoak, 1978;Jamieson & Petrusic, 1975;Marks, 1972).…”
Section: Relational Comparisons Without Explicit Relationsmentioning
confidence: 99%
“…Note, however, that this attentional hypothesis predicts the wrong pattern of same RTs in the same-stimulus conditions. According to most of the theories of attentional focus that address the issue of perceptual variability, placing attention in a given region results in reduced perceptual variability in that region (e.g., Ashby, Prinzmetal, Ivry, & Maddox, 1996;Luce, Green, & Weber, 1976;Tsal & Shalev, 1996). Such an attentional process would be adaptive for better discriminating among the highly similar objects that occur in the dense regions, for example, pair (1, 2) in Condition 1.…”
Section: Red (R) Green (G) and Blue (B) Values And Approximate Colomentioning
confidence: 99%
“…Ennis (1988Ennis ( , 1992 has provided formalizations of exemplar-memory models that incorporate this perceptual variability, and Ennis (1988) and Nosofsky (1988b) discussed the potential benefits of such approaches to understanding a variety of psychological phenomena. Certain types of perceptual selective attention phenomena may be well modeled within such an approach in terms of reduced variances of the perceptual distributions associated with attended stimuli or dimensions (e.g., Luce, Green, & Weber, 1976;Nosofsky, 1983). I believe that the perceptualdistribution approach is potentially most fruitful in designs involving highly confusable stimuli, where, even following protracted training, pairwise discriminations among objects axe poor.…”
Section: Introduction and Issues Regarding Selective Attentionmentioning
confidence: 99%